2019
DOI: 10.1093/mnras/stz958
|View full text |Cite
|
Sign up to set email alerts
|

A fast radio burst with frequency-dependent polarization detected during Breakthrough Listen observations

Abstract: Here, we report on the detection and verification of Fast Radio Burst FRB 180301, which occurred on UTC 2018 March 1 during the Breakthrough Listen observations with the Parkes telescope. Full-polarization voltage data of the detection were captured-a first for non-repeating FRBs-allowing for coherent de-dispersion and additional verification tests. The coherently de-dispersed dynamic spectrum of FRB 180301 shows complex, polarized frequency structure over a small fractional bandwidth. As FRB 180301 was detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 67 publications
1
31
1
Order By: Relevance
“…The detection of linear polarization allowed the measurement of the Faraday rotation measure (RM; see details in Methods). For seven bursts with polarization data recorded and S/N > 5 for the polarization intensity, we calibrated the data and found similar RM values ranging from 521.5 +4.6 −4.2 rad m −2 to 564.4 +3.4 −4.0 rad m −2 (with 68% confidence level), very different from that reported (−3163 ± 20 rad m −2 ) in the initial discovery 14 . It is possible that the previous reported RM value was biased oweing to the narrow signal bandwidth of 40 MHz (see Methods).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The detection of linear polarization allowed the measurement of the Faraday rotation measure (RM; see details in Methods). For seven bursts with polarization data recorded and S/N > 5 for the polarization intensity, we calibrated the data and found similar RM values ranging from 521.5 +4.6 −4.2 rad m −2 to 564.4 +3.4 −4.0 rad m −2 (with 68% confidence level), very different from that reported (−3163 ± 20 rad m −2 ) in the initial discovery 14 . It is possible that the previous reported RM value was biased oweing to the narrow signal bandwidth of 40 MHz (see Methods).…”
mentioning
confidence: 63%
“…We carried out four observations for this source in July, September and October 2019 with a total observing time of 12 h (see Extended Data Table 1) using the 19-beam receiver mounted on FAST, covering the frequency range of 1000 − 1500 MHz. In the July and September sessions, the center beam (with a 3 beam size at full-width-half-maximum, FWHM) of the 19-beam receiver was pointed at the previously reported position (right ascension, α = 06 h 12 m 43.4 s ; declination, δ = +04 • 33 45.4 ) from the Parkes discovery observation 14 (where the telescope's FWHM beam size was 14.1 ). Four bursts were detected using Beam 7 in the July session, where we only recorded two linear polarization channels.…”
mentioning
confidence: 99%
“…With new FRBs likely detected with the UWL receiver at Parkes, more with the multibeam observations as part of the Breakthrough Listen (Price et al 2019) and SUPERB observations, and further searches through archival Parkes data (e.g., Zhang et al 2019), we expect that the Parkes telescope will continue to increase the known population of FRBs albeit with limited localisation potential.…”
Section: Discussionmentioning
confidence: 97%
“…So far, polarization has been measured for only eight FRBs, of which five have measured RMs, two with no measurement, and one with an RM estimate consistent with zero (see overview by Caleb et al (2018) and Price et al (2019) for discussion of unusual polarization of FRB 180301). Of the eight FRBs, three have a very high polarization degree (> 80 per cent), including the first repeating FRB (Michilli et al 2018).…”
Section: Implications Of the Frb Polarimetrymentioning
confidence: 99%
“…The repeating FRB 121102 shows 100% linear polarization while 0% circular polarization. Another repeating FRB, FRB 180301 showed 30% linear polarization and 70% circular polarization during its initial detection at the Parkes Radio Telescope (Price et al, 2019). However, during the follow-up observations with the FAST telescope, Luo et al (2020) found up to 80% linear polarization.…”
Section: Polarizationmentioning
confidence: 95%